Subtract (9x^2 + 3x – 4) – (3x^2 +8x – 1)

Subtract (9x^2 + 3x – 4) – (3x^2 +8x – 1) = 6x^2-5x-3

Question

Asked 4/16/2013 12:17:40 PM

Updated 4/5/2014 2:50:04 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [4/5/2014 2:50:03 PM], Confirmed by andrewpallarca [4/5/2014 2:50:04 PM]

Rating

There are no new answers.

Solve 3x - 8.5 = 2.5x – 1.25 - .75x for x.

Question

Not Answered

Updated 4/5/2014 2:49:19 PM

2 Answers/Comments

3x - 8.5 = 2.5x – 1.25 - .75x ;

3x - 8.5 = 1.75x - 1.25;

3x - 1.75x = -1.25 + 8.5;

1.25x = 7.25;

x = 7.25/1.25;

x = 5.8

3x - 8.5 = 1.75x - 1.25;

3x - 1.75x = -1.25 + 8.5;

1.25x = 7.25;

x = 7.25/1.25;

x = 5.8

Added 4/5/2014 2:48:02 PM

This answer has been confirmed as correct and helpful.

3x-4=2x-4/3;

3x - 2x = -4/3 + 4;

x = 8/3

3x - 2x = -4/3 + 4;

x = 8/3

Added 4/5/2014 2:49:19 PM

This answer has been confirmed as correct and helpful.

27,105,351

questions answered

There are no comments.